(untitled) (American International Journal of Education and Linguistics Research, 2021)
E-learning is a process of learning where we use the electronic-based platform through the internet. Nowadays, e-learning has become very essential for academia and vocational skills training through the use of the internet. During the ongoing lockdown, the Ministry of Education of Bangladesh is conducting online classes through various e-learning platforms. Education activities have been completed through e-learning but technical education is lagging in Bangladesh in the new-norm situation. With this backdrop, the study has developed a model for teaching tailoring curriculum to train the tailors’ course to participants in selected areas of Bangladesh. The approach of this research is classroom action research in e-platform involving teachers to examine common issues. Teachers have followed the three learning domains (Cognitive, affective & psychomotor domains) to make the students skilled in tailoring via e-platform. The study will show how the new teaching method was applied using e-platform and the impact of the proposed teaching method in the gradual improvement of the psychomotor skill in the tailoring of the students. This study implies the NSD program of the Ministry of Education. It is expected that the study will help to improve psychomotor skills by a proposed teaching system using an e-platform in the new-norm situation.